Relationship Between The Level Of Physical Fitness And The Learning Achievement Of Students In SDN 1 Sidorejo - Radistya Dio Mahendra; Nur Subekti (JUARA : Jurnal Olahraga, 2024)
This research aims to explore the correlation and influence of students' physical fitness levels on their learning achievement in Physical Education, Sports, and Health (PESH) subjects. The study was conducted at SDN 1 Sidorejo and employed correlation methods using Pearson product-moment statistics. The research population consisted of 40 students from grades I to VI, with a sample of 32 students from grades III to VI, selected through purposive sampling. The data analysis process consisted of two main stages: (1) Verification of classical assumptions, such as normality testing using Shapiro-Wilk and linearity testing, and (2) Hypothesis testing through Pearson Product Moment correlation tests. Furthermore, simple linear regression analysis was conducted to assess the extent of the influence of physical fitness on student learning achievement. Findings from this study indicate a positive relationship between physical fitness levels and student learning achievement in Physical Education, Sports, and Health at SDN 1 Sidorejo. Support for these findings was obtained from Pearson Product Moment correlation test results, showing a significance value (2-tailed) of 0.000 < 0.05, and a correlation coefficient (r) value of 0.651, exceeding the critical value of 0.349. Additional analysis using simple regression testing also yielded a significance value (2-tailed) of 0.000 < 0.05 and a t-value of 4.696, exceeding the critical value of 2.042. Therefore, it can be concluded that physical fitness levels have an impact on student learning achievement in PESH subjects at SDN 1 Sidorejo.